2014
DOI: 10.4028/www.scientific.net/amr.971-973.516
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization Technique for Non-Linear Free Vibrations Analysis of FGM Rectangular Plates

Abstract: In the present study, the problem of geometrically nonlinear free vibrations of functionally graded rectangular plates (FGRP) is studied. A homogenization technique has been developed to reduce the FGRP problem under consideration to that of isotropic homogeneous rectangular plate. The material properties of the functionally graded composites examined herein are assumed to be graded in the thickness direction of the plate and estimated through the rule of mixture. The proposed theoretical model is based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…2 shows the non dimensional non-linear maximum displacement W*max of FG square plate (N=1, =0° and =1) versus the nonlinear frequency ratio. The comparison made between the results obtained in reference [3] and the present ones shows a good agreement.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…2 shows the non dimensional non-linear maximum displacement W*max of FG square plate (N=1, =0° and =1) versus the nonlinear frequency ratio. The comparison made between the results obtained in reference [3] and the present ones shows a good agreement.…”
Section: Resultssupporting
confidence: 85%
“…The aim of this section is to apply the theoretical model presented in ref [3] and [4] Fig. 2 shows the non dimensional non-linear maximum displacement W*max of FG square plate (N=1, =0° and =1) versus the nonlinear frequency ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The axial displacements u and v are neglected considering the analysis made in reference [13]. The expression for the bending strain energy V b , the membrane strain energy V m , the coupling strain energy V c and the kinetic energy T are given in rectangular coordinate in reference [9]. The skew co-ordinates are related to the rectangular co-ordinate (ξ,η) by: ξ=x-y tanθ ; η=y/cosθ.…”
Section: Geometrically Non-linear Free Vibration Of Fully Clamped Fgspmentioning
confidence: 99%
“…The results obtained revealed that the temperature field and gradient index have significant effect on the nonlinear vibration of the FG plate. Boukhzer et al [9] presented a homogenization technique for the non-linear free vibrations analysis of FG rectangular plates. A homogenization technique has been developed to reduce the FGRP problem under consideration to that of an isotropic homogeneous rectangular plate.…”
Section: Introductionmentioning
confidence: 99%
“…A homogenisation procedure already proposed in [6][7][8][9] for the case of rectangular plates and beams, is used to reduce the problem studied to that isotropic homogeneous cracked beams, in order to show the effect of the crack and the volume fraction on structural dynamic characteristics such as natural frequencies.…”
Section: Introductionmentioning
confidence: 99%